Partial correction of immunodeficiency by lentiviral vector gene therapy in mouse models carrying Rag1 hypomorphic mutations - Castiello, Maria Carmina; Di Verniere, Martina; Draghici, Elena; Fontana, Elena; Penna, Sara; Sereni, Lucia; Zecchillo, Alessandra; Minuta, Denise; Uva, Paolo; Zahn, Marco; Gil-Farina, Irene; Annoni, Andrea; et al. (Frontiers in Immunology, 2023)
Recombination activating genes (RAG) 1 and 2 defects are the most frequent form of severe combined immunodeficiency (SCID). Patients with residual RAG activity have a spectrum of clinical manifestations ranging from Omenn syndrome to delayed-onset combined immunodeficiency, often associated with granulomas and/or autoimmunity (CID-G/AI). Lentiviral vector (LV) gene therapy (GT) has been proposed as an alternative treatment to the standard hematopoietic stem cell transplant and a clinical trial for RAG1 SCID patients recently started. However, GT in patients with hypomorphic RAG mutations poses additional risks, because of the residual endogenous RAG1 expression and the general state of immune dysregulation and associated inflammation. In this study, we assessed the efficacy of GT in 2 hypomorphic Rag1 murine models (Rag1F971L/F971L and Rag1R972Q/R972Q), exploiting the same LV used in the clinical trial encoding RAG1 under control of the MND promoter. Starting 6 weeks after transplant, GT-treated mice showed a decrease in proportion of myeloid cells and a concomitant increase of B, T and total white blood cells. However, counts remained lower than in mice transplanted with WT Lin- cells. At euthanasia, we observed a general redistribution of immune subsets in tissues, with the appearance of mature recirculating B cells in the bone marrow. In the thymus, we demonstrated correction of the block at double negative stage, with a modest improvement in the cortical/medullary ratio. Analysis of antigen-specific IgM and IgG serum levels after in vivo challenge showed an amelioration of antibody responses, suggesting that the partial immune correction could confer a clinical benefit. Notably, no overt signs of autoimmunity were detected, with B-cell activating factor decreasing to normal levels and autoantibodies remaining stable after GT. On the other hand, thymic enlargement was frequently observed, although not due to vector integration and insertional mutagenesis. In conclusion, our work shows that GT could partially alleviate the combined immunodeficiency of hypomorphic RAG1 patients and that extensive efficacy and safety studies with alternative models are required before commencing RAG gene therapy in these highly complex patients.